2021
DOI: 10.1111/cas.15159
|View full text |Cite
|
Sign up to set email alerts
|

Non‐metabolic function of MTHFD2 activates CDK2 in bladder cancer

Abstract: Bladder cancer is a common tumor with a high recurrence rate and high fatality rate, and its mechanism of occurrence and development remains unclear. Many proteins and metabolites reprogram at different stages of tumor development to support tumor cell growth. The moonlighting effect happens when a protein performs multiple functions simultaneously in a cell. In this study, we identified a metabolic protein, MTHFD2, which participates in the cell cycle by binding to CDK2 in bladder cancer. MTHFD2 has been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Meanwhile, MTHFD2 could accelerate tumorigenesis and metastasis via the AKT/glycogen synthase kinase-3β (GSK-3β)/β-catenin signaling pathway in lung adenocarcinoma [ 19 ] and via the STAT3 signaling pathway in ovarian cancer [ 20 ]. Recently, MTHFD2 was found to affect bladder cancer cell growth by activating CDK2 [ 21 ]. All these observations indicated that MTHFD2 is tightly associated with the tumorigenesis of various cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, MTHFD2 could accelerate tumorigenesis and metastasis via the AKT/glycogen synthase kinase-3β (GSK-3β)/β-catenin signaling pathway in lung adenocarcinoma [ 19 ] and via the STAT3 signaling pathway in ovarian cancer [ 20 ]. Recently, MTHFD2 was found to affect bladder cancer cell growth by activating CDK2 [ 21 ]. All these observations indicated that MTHFD2 is tightly associated with the tumorigenesis of various cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…MTHFD2 is also a metabolic checkpoint linking purine metabolism to autoimmune responses ( Sugiura et al, 2022 ). It is highly expressed in various cancers, playing a role in metabolic remodeling and regulating of the cell cycle in the mitochondria and nucleus, respectively ( Lee et al, 2021b ; Liu et al, 2021 ; Yao et al, 2021 ; Ren et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations have been associated with advanced tumor stage and grade [ 105 ]. In breast cancer, up-regulation of MTHFD2, which contributes in the cell cycle through binding to CDK2, has been associated with shorter OS, tumor grade and stage [ 107 ]. Other studies have shown up-regulation of a number of CDK2-interactiong circRNAs such as hsa_circ_0000520 [ 128 ], circ_0084927 [ 129 ] and circZFR [ 130 ] in cervical cancer patients.…”
Section: Cyclin-dependent Kinase 2 (Cdk2)mentioning
confidence: 99%